Self Efficacy terhadap Psychological Well-Being Orang Tua Anak Thalasemia Mayor di RSUD Al-Ihsan Provinsi Jawa Barat - Yuyun Sarinengsih; Novita Ts; Denni Fransiska (Malahayati Nursing Journal, 2025)
ABSTRACT Thalassemia is a genetic blood disorder that requires children to undergo intensive medical treatment throughout their lives and parents of children with thalassemia major often face severe psychological challenges. As individuals who play a key role in their child's care and medical treatment, their self-efficacy can play an important role in maintaining psychological well-being. This study aims to examine the effect of self-efficacy on psychological well-being of parents of children with thalassemia major. This research method uses quantitative methods with a cross sectional approach to correlational design. Samples of 50 parents who have children with thalassemia major using the modified Bandura GSES instrument for self-efficacy and CW-PSWBS for PWB, Univariate analysis of frequency distribution and bivariate analysis of Pearson parametric test. The results showed that there is a correlation between self efficacy and psychological well-being of parents of thalassemia major children at Al-Ihsan Hospital, West Java Province (r=0.836, p0.005). It is necessary to have family support for parents with thalassemia major children to improve and maintain parents' self efficacy and psychological well-being. The results of this study explain that there is a correlation between self efficacy and psychological well-being of parents of thalassemia major children at Al-Ihsan Hospital, West Java Province. Keywords: Parents, Psychological Well-Being, Self-Efficacy, Thalassemia Major Children  ABSTRAK Thalassemia adalah penyakit kelainan darah genetik yang mengharuskan anak-anak untuk menjalani perawatan medis yang intensif sepanjang hidup mereka sehingga orang tua yang mempunyai anak dengan thalasemia mayor sering menghadapi tantangan psikologis yang berat. Sebagai individu yang memegang peran kunci dalam pengasuhan dan perawatan medis anak, self-efficacy mereka dapat berperan penting dalam menjaga kesejahteraan psikologis. Penelitian ini bertujuan untuk mengkaji pengaruh self-efficacy terhadap psychological well-being orang tua anak dengan thalasemia mayor. Metode penelitian ini menggunakan metode kuantitatif dengan desain korelasional pendekatan cross sectional. Sampel 50 orang tua yang mempunyai anak thalasemia mayor dengan menggunakan instrument Bandura GSES modifikasi untuk self efikasi dan CW-PSWBS  untuk PWB. Analisis univariat distribusi frekuensi dan analisis bivariat uji parametric Pearson. Hasil penelitian menunjukkan bahwa adanya korelasi antara self efficacy terhadap psychological well-being  orang tua  anak  thalasemia mayor di RSUD Al-Ihsan Provinsi Jawa Barat (r=0,836, p0,005). Perlu adanya dukungan keluarga terhadap orang tua dengan anak thalasemia mayor untuk meningkatkan dan mempertahankan self efficacy dan psychological well-being orang tua. Hasil penelitian ini menjelaskan bahwa adanya korelasi antara self efficacy terhadap psychological well-being  orang tua  anak  thalasemia mayor di RSUD Al-Ihsan Provinsi Jawa Barat. Kata Kunci:  Anak Thalasemia Mayor, Orang Tua, Psychological Well Being, Self-Effication